PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, DAN INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) (STUDI EMPIRIS PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Alfin Irsyad Khoiron; Endah Suwarni; Basuki Rachmat (Jurnal Akuntansi Bisnis dan Humaniora, 2023)
The purpose of this study is to investigate the influence of Profitability, Leverage, Company Size and Intensity of Fixed Assets on the Tax Avoidance of subsector food and beverage companies. The research used Purposive Sampling as the data collection technique. From the 30 companies, there were only 14 companies which met the criteria. The data analysis method used a multipe linear regressions. The used 26th version of IBM SPSS Statistics as a data analysis tool. The result of the research showed that there was a postive and significant influence of Company Size on the Tax Avoidance. Meanwhile, Profitability, Leverage, and Intensity of Fixed Assets partially have not significant effect on the Tax Avoidance. The result ofsimultaneous test showed that there was a not significant influence of Profitability, Leverage, and Intensity of Fixed Assets on the Tax Avoidance.